Accessibility of information about oral health and dental care to pregnant women in Vilnius - PŪRIENĖ, Alina; GRYBIENĖ, Rita; BOND, Birutė; ŽEKONIENĖ, Jūratė; PEČIULIENĖ, Vytautė; MANELIENĖ, Rasmutė (Acta medica Lituanica, 2011)
Background. The aim of the present study was to evaluate the accessibility of information about oral health and dental care to pregnant women in Vilnius. Materials and methods. An anonymous questionnaire was distributed to 363 pregnant women in the city of Vilnius. The response rate was 79%. The respondents were divided into groups according to their education, marital status, occupation, the dental office they visit, the source of information used, knowledge about oral health influence on the fetus’ health, and complications during previous pregnancies. Results. The mean age of the respondents was 27.52 ± 0.62 years. Of them, 83.5% during their pregnancy visited a dental clinic on a regular basis; 60.63% of women were aware of the fact that oral health affected the condition of their fetus; 75% of pregnant women noted they would derive the information concerning oral health and dental care during pregnancy from popular literature rather than from medical professionals. Women attending private dental practice obtained more information from side sources than did patients of a public dental practice (81.9% and 63.8%, respectively; p < 0.014); 60.6% of respondents received information about oral health and dental care during pregnancy from their gynecologist; 25.7% of respondents noted that they had not received any information on oral or dental care during pregnancy. Conclusions. In general, information about dental care was available to all pregnant women that participated in the study. The information in respect of oral health and dental care obtained from dentists was not sufficient. The main source of information about oral care received by the women surveyed during pregnancy was a gynecologist and other sources such as journals, the internet, books, etc. Keywords: pregnancy, dental care, information sources, fetus’ health